MICROMORPHOLOGICAL ANALYSIS OF THE AERIAN ORGANES OF MARRUBIUM ALYSSON L. FROM FLORA OF TUNISIA - F. K. Serebryanaya; G. Zayer (Фармация и фармакология (Пятигорск))
The micromorphological investigations of Marrubium alysson L. growing on the territory of the Tunisian Republic have been conducted. The aim of the study was to conduct comparative ecological and morphological researches of Marrubium alysson aerian parts, to study an anatomical structure of caulifoliary system elements including stems, petioles, leaf margins a structure of the epidermis. Materials and methods. As an object of the research, dried-up herb and herbarium specimens of Marrubium alysson L., growing on the territory of the Tunisian Republic, were used. The micromorphological investigations were conducted by morphological and histochemical methods. Results and discussion. Comparative ecological and morphological researches have been conducted. The anatomic structure of the elements of the caulifoliary system including stems, petioles, leaf margins has been studied. The anatomic structure of the epidermis has been studied, too. The diacytic type of the stomatal apparatus, numerous branched trichomes with multicellular basis, located both on top and lower leaf parts have been found out. The conducted researches are a fragment of complex researches of perspective raw plants of Tunisian flora. Conclusion. Comparative eсological and micromorphological researches have been conducted, the anatomic structure of the stems, petioles, leaf margins, and also the epidermis structure of top and lower leaf parts has been also carried out. The diacytic type of the stomatal apparatus, trichomes with multicellular basis located both on top and lower leaf parts have been found out. The collenchyme is located in the subepidermal zone of a stem, petioles and in the zone of the central vein of a limb. The revealed signs can be included into product specification files on herbal raw materials